2021
DOI: 10.3389/fendo.2021.774309
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CTRP7 Is a Potential Predictor for Metabolic Syndrome

Abstract: BackgroundPrevious animal studies have revealed that CTRP7 is related to energy metabolism. However, little is known regarding the relationship between CTRP7 and metabolic diseases in humans. Hence, this study was designed to explore the association between CTRP7 and MetS through a cross-sectional study and multiple intervention studies.MethodsA total of 624 individuals were enrolled in this study. The levels of CTRP7 and APN were determined by ELISA kit. HEC, OGTT and lipid infusion were performed in heathy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…OGTT was performed for study individuals at 8:00 am. after fasting for 12 h. Venous blood samples were drawn for GPHB5, adiponectin, glucose, and insulin ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OGTT was performed for study individuals at 8:00 am. after fasting for 12 h. Venous blood samples were drawn for GPHB5, adiponectin, glucose, and insulin ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The kit is highly sensitive and specific for the determination of human GPHB5 and is not interfered with by other cytokines. Serum adiponectin levels were also measured by an ELISA kit from Aviscerabio science Inc., USA (sk00010-01), with intra- and inter-assay CV of 4% - 8% and 8% - 12%, respectively, as previously reported ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The cluster Profiler package was used for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. Visualization of the PPI network was constructed by Cytoscape ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Euglycemic-hyperinsulinemic clamp (EHC) studies were performed in all individuals as previously published (18). Experimental design.…”
Section: Ogtts and Ehcsmentioning
confidence: 99%
“…Metabolic syndrome (MetS), also known as insulin resistance (IR) syndrome, is one of the metabolic disorders with a high risk of negative cardiovascular outcomes, including obesity, hypertension, dyslipidemia, and impaired glucose tolerance (IGT) (7,8). Recent studies indicated that genes like CTRP7 and SPTAN1 are associated with the occurrence of MetS (9,10). In addition, various serological indicators were proved to be the potential biomarkers for the diagnosis of MetS (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%